2018
DOI: 10.1039/c8ob00662h
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of substituted diaryl sulfones via a [3 + 3] benzannulation strategy

Abstract: A base-mediated [3 + 3] benzannulation strategy for the conversion of 1,3-bis(sulfonyl)propenes and β,γ-unsaturated α-ketoesters to diaryl sulfones has been developed. This method provides facile, metal-free and efficient access to highly substituted diaryl sulfones in good to excellent yields. In addition, the sulfonyl group could be easily removed or converted to other functional groups via an organostannane intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The known compounds 1a–1b , 1e , 1f–1n , 1o , 4a , 4e , 4g , 4j , 4k , and 4s were prepared according to reported procedures, and all the spectra data are in agreement with the reports.…”
Section: Experimental Sectionmentioning
confidence: 71%
“…The known compounds 1a–1b , 1e , 1f–1n , 1o , 4a , 4e , 4g , 4j , 4k , and 4s were prepared according to reported procedures, and all the spectra data are in agreement with the reports.…”
Section: Experimental Sectionmentioning
confidence: 71%
“…[39] Encouraged by Singarapu and Menon's study, Yan and Zhang reported a DBU-promoted (3 + 3) benzannulation reaction of 1,3-bis(sulfonyl)propenes 70 and β,γ-unsaturated α-ketoesters 76 to give diaryl sulfones 77 in good yields (Scheme 15a). [40] This strategy provided a facile, metal-free, and efficient procedure for the synthesis of highly substituted diaryl sulfones in excellent yields. Furthermore, the similar DBUpromoted (3 + 3) benzannulation reaction of 1,3-bissulfonyl propenes 70 and Morita-Baylis-Hillman (MBH) bromides 78 was also realized (Scheme 15b).…”
Section: Tertiary Amine-mediated Benzannulation Reactionsmentioning
confidence: 99%
“…By adding D 2 O (20 equiv) to the reaction system, 93 % of hydrogen atoms were replaced by deuterium at the 5‐position on the benzene ring. Based on the result of the deuterium‐labeling experiment and previous studies, a plausible mechanism for this [4+2] benzannulation reaction was proposed (Scheme ). In the presence of DABCO, the Nazarov reagent was deprotonated to form intermediate A , which could continuously undergo 1,6‐addition to dienic sulfone 1 h to afford intermediate C .…”
Section: Figurementioning
confidence: 99%
“…B ya dding D 2 O( 20 equiv) to the reaction system, 93 % of hydrogen atoms were replaced by deuterium at the 5-position on the benzene ring. Based on the result of the deuterium-labeling experiment and previous studies, [12,13] With the elimination of sulfonyl,t he benzannulation process results in the formation of product 3.…”
mentioning
confidence: 97%